BIODIVERSITY OF CAUCASIAN DESERTS AND SEMI-DESERTS (Conferencea, 2024)
From the geological point of view, the deserts and semi-deserts of the Caucasus are represented in the territory freed from the waters of the Caspian Sea several tens of thousands of years ago. In Transcaucasia, the biome of deserts and semi-deserts occupies a vast area of the Mtkvar-Arax depression. In the west, in the form of a semi-desert, it extends to the meridian of Tbilisi (it ends at Rustavi). Within the limits of Eastern Georgia, we find only semi-deserts with separate fragments of salted (loamy soil) deserts. In addition to floristic elements, the transition of deserts to semi-deserts in the territory of Eastern Georgia is clearly evidenced by the impoverishment of Psilodea hyperxerophilous taxa (Gegechkor, 2008). A detailed faunal survey of the arid regions of the Caucasus fully confirmed the presence of the Mtkvar Arax depression and in the Middle of the river Araxis the diversity of desert taxons characteristic of Iran-Turanian deserts.